ANALISIS SPK PENERIMA BANSOS PKH DENGAN METODE SAW PADA DINAS SOSIALDUKCAPIL PROVINSI JAMBI - Fadhliazis, Fadhliazis; Husni, Akhmad Faisal (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
There are so many programe is given by goverment to tackle proverty. One of them is Program Keluarga Harapan (PKH). But, data of beneficiery receiver is not suitable yet as something that hope. The reason is not optimal act of determining status. Although, beneficiery receiver is not on target. Application prototype planner system to support final decision for PKH beneficiery receiver is used to take decision is Simple Addictive Weighting System (SAW). It wears Use Case Diagram, Activity Diagram, and Class Diagram as model of system planner. Which is result assessment is done by system. That have two measurment, proper or not proper. SAW Method is choosen because of this method can determine quality grade each atribute. Then, continue with rank process will do to select best alternative from a lot of alternatives. Such as; poor family which is include proper category based on some criterias is defineted. With that rank process, assesment will be appropriate because based on criteria grade and quality grade that determine alternative. It will get proper result. The result will be come holder for Social, Population, and Civil Registration department in Jambi Province. The assesment can be used to measure poor family that proper to get PKH beneficiery. Which is this data will be given to the Ministry of Social Services of Indonesia Republic later. It become proper data for goverment to give the PKH beneficiery is on the target.